Find the height of the tower, Mathematics

The angle of elevation of the top of a tower standing on a horizontal plane from a point A is α .After walking a distance d towards the foot of the tower the angle of elevation is found to be β . Find the height of the tower. (Ans: d/cot α - cot β)

459_horizontal plane.png

Ans: Let BC = x

tan β =  AB/CB

tan β = h/x

x = h/tan β

x = h cot β     ---------(1)

tan α = AB/DC CB

tan α = h /d + x

d + x = h/tan α  = hcotα

x = h cot  α - d ----------(2)

from 1 and 2

h cot β =  h cot  α - d

h (cot α - cot β ) = d

h = d /cot α - cot β

 

Posted Date: 4/10/2013 2:10:51 AM | Location : United States







Related Discussions:- Find the height of the tower, Assignment Help, Ask Question on Find the height of the tower, Get Answer, Expert's Help, Find the height of the tower Discussions

Write discussion on Find the height of the tower
Your posts are moderated
Related Questions
In my wallet there is a 10p stamp, a 12p stamp and a 20p stamp.I remove a stamp,put it back and then remove a stamp again.Draw a sample space diagram to show all the possible resul

To solve out linear equations we will make heavy use of the following facts. 1. If a = b then a + c = b + c for any c.  All it is saying that we can add number, c, to both sides

Example of Imaginary Numbers: Example 1: Multiply √-2  and √-32 Solution: (√-2)( √-32) = (√2i)( √32i) =√64 (-1) =8 (-1) =-8 Example 2: Divid


ALGORITHM FOR DIVISION : If you ask a 10 or 1 1-year-old child to solve, say, 81 + 9, the chances are that she will correctly do it. But if you ask her to solve, say 72 + 3, t

If α & ß are the zeroes of the polynomial 2x 2 - 4x + 5, then find the value of a.α 2 + ß 2   b. 1/ α + 1/ ß  c. (α - ß) 2 d. 1/α 2 + 1/ß 2    e.  α 3 + ß 3 (Ans:-1, 4/5 ,-6,

Find the equation of the plane through (2, 1, 0) and parallel to x + 4y   3z = 1.

how do they solve log9 = ... 27

Reduction -when the original amount and the balance or remainder are known, to find the part that has been given away. (e.g., there were 15 toffees in a container, and there are

y(x) = x -3/2 is a solution to 4x 2 y′′ + 12xy′ + 3y = 0 , y (4) = 1/8 , and y'(4) = -3/64 Solution :  As we noticed in previous illustration the function is a solution an